ChemInform Abstract: Tetrabutylammonium Iodide‐Catalyzed Oxidative Coupling of Enamides with Sulfonylhydrazides: Synthesis of β‐Keto‐Sulfones. Issue 44 (15th October 2015) - Tang, Yucai; Zhang, Ye; Wang, Kaifeng; Li, Xiaoqing; Xu, Xiangsheng; Du, Xiaohua
Abstract A novel protocol for the catalyst‐ and base‐free synthesis of pharmaceutically interesting β‐keto sulfones is developed.